Environmental Performance and Firm Value: Testing the Role of Firm Reputation in Emerging Countries - Khanifah, Khanifah; Udin, Udin; Hadi, Nor; Alfiana, Fitri (International Journal of Energy Economics and Policy, 2019)
This study aims to analyze the empirical evidence about the effect of environmental performance on firm value mediated by firm reputation in emerging countries. The sample of this study is the mining industry sectors listed on the Indonesia Stock Exchange from 2015 to 2018. The data is analyzed using partial least squares based structural equation modeling (PLS-SEM) with WarpPLS 6.0 software. The results show that environmental performance has a positive and significant effect on firm reputation. In contrast to the expectation, environmental performance has a negative and significant effect on firm value. Firm reputation further becomes a significant mediator in the relationship between environmental performance and firm value. These findings recommend for future studies to expand the objects and extend the observation period. Keywords: environmental performance, firm reputation, firm value JEL Classifications: G32, K32, Q56, L14 DOI: https://doi.org/10.32479/ijeep.8490